Residual efficacy of spinetoram on wheat and maize against Rhyzopertha dominica and Sitophilus oryzae. (January 2022) - Ksoura, T.; Agrafioti, P.; Tsiropoulos, N.G.; Athanassiou, C.G.
Abstract: In the present work, we evaluated the residual efficacy of spinetoram on grains (wheat and maize) against two stored product insect species, Rhyzopertha dominica (F.) (Coleoptera: Bostrychidae) and Sitophilus oryzae (L.) (Coleoptera: Curculionidae). All bioassays were conducted with spinetoram at different dose rates, 0.1, 1 and 10 ppm. The treated grains were kept in controlled conditions 25 °C and 65%, five months, in order to investigate the insecticidal effect of spinetoram. Spinetoram residues were measured at 1 ppm right after the application and during the last month. For both tested species, adult mortality was evaluated in the treated grains after 7 and 14 days of exposure. After the termination of the exposure, progeny production (65 d later) was counted. The most susceptible species was R. dominica for both tested commodities, given that mortality was reached 100% even after 7 days of exposure at the lowest dose rate of 0.1 ppm. Regarding progeny production numbers of R. dominica were suppressed, in contrast with S. oryzae, in which survival was high even at 10 ppm. Based on our results, spinetoran was quite effective on maize (86.6%) than on wheat (80.0%); however, the insecticidal efficacy remained stable for 5 months after the treatment at the tested conditions. Hence, the formulation remained stable for the whole storage period. Highlights: Spinetoram was effective against, for both species tested, Rhyzopertha dominica and Sitophilus oryzae . For both tested commodities, the most susceptible species was R. dominica . Spinetoram formulation remained stable for the whole storage period (5 months).